A PIK3CA transgenic mouse model with chemical carcinogen exposure mimics human oral tongue tumorigenesis. Issue 1 (21st May 2020) - Tan, Melody T.; Wu, Jean G.; Callejas‐Valera, Juan Luis; Schwarz, Richard A.; Gillenwater, Ann M.; Richards‐Kortum, Rebecca R.; Vigneswaran, Nadarajah
Summary: Oral cancer causes significant global mortality and has a five‐year survival rate of around 64%. Poor prognosis results from late‐stage diagnosis, highlighting an important need to develop better approaches to detect oral premalignant lesions (OPLs) and identify which OPLs are at highest risk of progression to oral squamous cell carcinoma (OSCC). An appropriate animal model that reflects the genetic, histologic, immunologic, molecular and gross visual features of human OSCC would aid in the development and evaluation of early detection and risk assessment strategies. Here, we present an experimental PIK3CA + 4NQO transgenic mouse model of oral carcinogenesis that combines the PIK3CA oncogene mutation with oral exposure to the chemical carcinogen 4NQO, an alternate experimental transgenic mouse model with PIK3CA as well as E6 and E7 mutations, and an existing wild‐type mouse model based on oral exposure to 4NQO alone. We compare changes in dorsal and ventral tongue gross visual appearance, histologic features and molecular biomarker expression over a time course of carcinogenesis. Both transgenic models exhibit cytological and architectural features of dysplasia that mimic human disease and exhibit slightly increased staining for Ki‐67, a cell proliferation marker. The PIK3CA + 4NQO model additionally exhibits consistent lymphocytic infiltration, presents with prominent dorsal and ventral tongue tumours, and develops cancer quickly relative to the other models. Thus, the PIK3CA + 4NQO model recapitulates the multistep genetic model of human oral carcinogenesis and host immune response in carcinogen‐induced tongue cancer, making it a useful resource for future OSCC studies.